Novel concept of data security using sliding image and image digest. (19th May 2022) - Singhal, Neha; Pathak, Vibhakar
Abstract: We are living in the tech world and information or data centers are growing day by day. Even the government departments are coming with the online portals and more rapid computerization, which enables them to get the data as well as to send the important data and report, online from anywhere in the world. With the ease, also comes some security issues, like how to keep the data protected from unauthorized access. For this purpose, we have proposed the security model in which we have enhanced the security in two phases, one is the authentication phase where the slider-based image partition concept is used and second phase is the message sharing module in which authentication key is used, which is generated using the Image and Message MD5 is also very strong. The SHA-512 hash of the image will be stored in the database which will act as IMAGE DIGEST for the verification purpose at the receiver end. When the receiver receives the image, the SHA-512 function will again operate over the received image, if both the image matches with HASH which is generated at the user end image HASH stored in database, then the image is considered valid at receiver end. Similarly, the message digest for the message can also be generated as stored in the database for the verification purpose. The generated authentication keys are tested with the previous approach using the various online and offline tools and results are better that the previous.